A Comprehensive Literature Survey on Research and Innovation in Robotics and Automation - Sandeep S Sarnobat (AG Volumes, 2022)
Every year, new developments in the robotics industry revolutionise the sector. Robotics' future will be shaped by these tendencies as Industry 4.0 takes hold in various sectors. In the early stages of the epidemic, companies and consumers alike began adopting robotic technology in a big way, and this trend continues to this day. Many parts of daily life may soon be controlled by robots thanks to recent developments in machine learning, AI, the Internet of Things (IoT), as well as the big data analysis techniques. Robotics and automation will have a major impact on the future, and so this study conducts a thorough literature analysis to examine the most recent developments as well as current research and developments.